Restoration of Vision following Long-Term Blindness: Considerations for Providing Rehabilitation. (January 2016) - Geruschat, Duane R.; Dagnelie, Gislin
The purpose of this article is to introduce the reader to a new area of research and practice known as vision restoration. The various approaches to restoration will be introduced and the implications of restored vision on rehabilitation strategies will be presented.